Memorable Socialism: Women's Voices from the Croatian Socialist Past - Potkonjak, Sanja (2007)
My paper is an attempt to invoke the history of women and is an attempt to understand diversity of women’ s everyday lives in socialism. It is also an invitation to look upon politics of women’ s memories as on to a form of confirmation of women’ s experience of history. It communicates with the past and the present of a minoritarian tradition, a tradition of women’ s memory. As an ethnography and professional regression into women’ s cultural, social, political and economical world of socialism, the text deals with the condition of memory, talks about fragility of remembrance, of the difficulties in evoking of relevant places in the every day life in socialism. It speaks about socialist memory-canon, and exclusion of women from it, as well as about strategies of inclusion or adding a gender perspective to a historical canon. The special goal of this paper is to argument an existence of plural and parallel histories of every day life in which even women participate each in her own way, parcelling the universal picture of femininity and the utopia of solidarity.
Projekt MZOS
ENG